Restorative Justice in Medical Disputes: Analyzing Responsiveness and Legal Neutrality Deficit from the Perspective of Healthcare Professionals - Johan, Willy; Fikri , Ahmad Ma’mun (Research Horizon, 2025)
The application of restorative justice in medical disputes in Indonesia faces significant structural obstacles. This study examines how healthcare professionals experience and perceive restorative justice, analyzes its vulnerabilities through the frameworks of responsive law and critical legal studies, and proposes a neutral, proportional model of dispute resolution, particularly through specialized medical adjudication, to address regulatory gaps that enable extortion risks and legal injustice. Using a phenomenological empirical-qualitative approach combined with statutory and critical legal analysis, the research evaluates the practical implementation of the Health Law (Law Number 17 of 2023). The findings show that restorative justice helps reduce adversarial litigation and protects the professional reputation of healthcare providers, who overwhelmingly prefer mediation to court proceedings. However, the lack of clear procedural limits and standardized restitution guidelines leaves practitioners vulnerable to misuse and disproportionate claims, causing the mechanism, intended to promote responsiveness, to drift toward repressive outcomes. This shift intensifies socio-economic inequalities and media-driven pressures, undermining legal neutrality and substantive justice. The study recommends the establishment of precise regulatory standards, independent oversight, and specialized medical adjudication mechanisms to ensure that restorative justice operates fairly, effectively, and in accordance with objective medical and legal principles.